Violence and Ethical Non-Violence: On Universality and Particularity - Azaovagh de la Rosa, Anisa (Analysis. Journal of Philosophical Research, 2019)
This article tries to show how Judith Butler situates violence within ethical theory, and associates it with three basic demands. The universality of the norms and values that are to guide moral judgments, positive or negative, but that may affect individual particularity and singularity. That is, that the moral subject be absolutely coherent with himself in his identity and in his conduct. This could negatively affect his freedom and the demand that the judgment of condemnation be morally absolute, leaving the condemned without an answer. In this context, the moral subject appears as a social construct in charge of an external power. It places it as patient or passive and forced to transform the effect of this external power on it, into an internal power that transforms it into an agent or an active one.